1981
DOI: 10.1364/ao.20.004263
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of temperature distribution of flames by moire deflectometry

Abstract: Mapping of temperature of a premixed hydrogen-oxygen flame by moire deflectometry is demonstrated. The technique is based on deflection mapping of rays from a collimated light beam due to gradients of the refractive index across the flame. For an axially symmetric flame the radial distribution of the refractive index was derived by Abel transformation. The temperature profile of the flame was calculated for a known gas composition assuming ideal gas behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…On the other hand, optical methods are mainly fast, non-intrusive and accurate [8]. There exists many optical methods such as Interferometry [9][10][11], Laser speckle technique [12], Schlieren photography [13][14][15] and Moiré deflectometry [16][17][18][19] that have been studied to obtain and visualize the temperature field of gaseous flames. All the interferometry methods, including Mach-Zehnder interferometry [20,21], Talbot interferometry [22][23][24][25] and Holographic interferometry [26,27] are based on changes in the refractive index of the gaseous products of the flame.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, optical methods are mainly fast, non-intrusive and accurate [8]. There exists many optical methods such as Interferometry [9][10][11], Laser speckle technique [12], Schlieren photography [13][14][15] and Moiré deflectometry [16][17][18][19] that have been studied to obtain and visualize the temperature field of gaseous flames. All the interferometry methods, including Mach-Zehnder interferometry [20,21], Talbot interferometry [22][23][24][25] and Holographic interferometry [26,27] are based on changes in the refractive index of the gaseous products of the flame.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, this technique has been mainly used in the structural visualization for low temperature [1,2], low and high speed complex flow fields [3][4][5], the density measurement [6], as well as the temperature measurement for the flow fields whose temperature is not too high [7]. Until now, it is rarely reported that this technology could be used in the structural visualization, or the temperature and the electron number density measurement for the high-temperature complex flow fields [8].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, OCT has played important roles in visualizing various flow [1] and hot flow fields [2,3], as well as being applied in measuring key parameters for various flow fields [1,[4][5][6][7]. In view of these advantages and applications of OCT, the feasibility of it on measuring flow velocity distribution of gas jet flow field is worthy to be analyzed.…”
Section: Introductionmentioning
confidence: 99%